2018
DOI: 10.1146/annurev-criminol-032317-092339
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Crime Trends Back into Criminology: A Critical Assessment of the Literature and a Blueprint for Future Inquiry

Abstract: Rates of street crime have dropped substantially over the past several decades, but important nuances of this decline are underappreciated and the reasons for it remain unclear. We suggest that the narrow conception of change adopted within criminology has hindered the field's capacity to develop a stronger scientific understanding of crime trends. Criminology has focused heavily on within-person changes in crime, devoting comparatively little attention to changes in aggregate crime rates. In this review, we m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 77 publications
2
86
0
Order By: Relevance
“…These socioeconomic, housing, and demographic shifts occurred alongside decreasing crime (Zimring 2007). This crime decline is well documented at the national and city levels (Baumer et al, 2018), although the downward trend within cities depends upon the time period (Baumer and Wolff, 2014;McDowall and Loftin, 2009). Few studies examine the crime drop within neighborhoods, and thus, the consequences of the crime decline for the ethnoracial patterning of neighborhood crime are unclear.…”
Section: The Dynamics Of the New Millenniummentioning
confidence: 99%
“…These socioeconomic, housing, and demographic shifts occurred alongside decreasing crime (Zimring 2007). This crime decline is well documented at the national and city levels (Baumer et al, 2018), although the downward trend within cities depends upon the time period (Baumer and Wolff, 2014;McDowall and Loftin, 2009). Few studies examine the crime drop within neighborhoods, and thus, the consequences of the crime decline for the ethnoracial patterning of neighborhood crime are unclear.…”
Section: The Dynamics Of the New Millenniummentioning
confidence: 99%
“…Time-series and panel studies are used to estimate the change in crime as a function of change in selected explanatory factors, one of which is usually the investigator's favorite. The findings become the basis for subsequent studies of crime trends, additional findings emerge, and finally they accumulate into a bigger list of findings about crime trends (see Baumer, Velez, and Rosenfeld, 2018). The study of crime trends has never been accused of being overly theoretical.…”
Section: Crime Trends and The Economymentioning
confidence: 99%
“…No comparable growth, acceptance, or advocacy is evident with respect to the study of changing crime rates. No one has proposed that the study of aggregate crime trends become the central paradigm of our field (although muted hints in that direction can be found in Baumer, Velez, and Rosenfeld, ; Rosenfeld, ). I have no intention of doing so here.…”
mentioning
confidence: 99%
“…This reasoning is based on a method of theory testing called discriminant predictability (e.g., Berg, ; Felson & Kreager, ; McGloin, Schreck, Stewart, & Ousey, ). Following Stinchcombe's () classic book on theory testing, it emphasizes the importance of determining exactly what category of behavior requires explanation (see also, Baumer et al, ) . Establishing the proper dependent variable (the “explanandum”) narrows down the possible theoretical explanations.…”
Section: Current Studymentioning
confidence: 99%
“…Opportunity exists when there is physical contact between vulnerable targets and motivated offenders in the absence of capable guardians. Similarly, Baumer, Velez, and Rosenfeld () suggested that crime rates tend to be high when controls are weak and when motivations to engage in crime are high (see also Baumer & Wolff, ; Berg, Baumer, Rosenfeld, & Loeber, ). Most explanations of trends in violence focus on changes in controls .…”
Section: Introductionmentioning
confidence: 95%